Kajian Teologis Pendampingan Orang Tua Terhadap Anak Dalam Belajar Dimasa Pandemik Coronaviruses Disease 2019 - Overianus Halawa; Manase Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The 2019 Coronavirus pandemic (covid-19) has damaged the order of human life as usual, including the world of education. In the world of education before the pandemic, parents completely handed over the responsibility of teaching to teachers in schools. But the COVID-19 pandemic has turned it into the responsibility of teaching left to parents. The problem is, many parents are not ready to teach because they are not equipped with teacher education. As a result, parents are forced to teach with minimal knowledge so that the actions of parents often become victims of this unpreparedness. Since the COVID-19 pandemic, there have been some parents who abuse their children because they are difficult to teach. Moving on from this case, the researcher is interested in providing solutions to the struggles of parents when accompanying children learn by using a qualitative approach by looking at the phenomena that occurred during the covid 19 pandemic. Based on the author's research, the right model for assisting parents in learning is teaching with repetitive, patient, and creative.